BARRIERS TO EMPLOYMENT OF MODERN CONTRACEPTION IN RURAL PERU - Maynard Tucker, Gisele (2015)
The paper studies the choice of contraceptive methods by a group of indigenous Quechua-speaking and living south of Cuzco, Peru, in a town of 3,500 inhabitants, of modest houses made of adobe. It is known from previous surveys that most women living in urban areas limit their family to 3 or 4 children, while in rural areas the average total fertility is 7.3 children (General Office of Census and Demography, 1979 - 1981 respectively ). It is known that 27% (N = 950) of the population of the saw used some method of contraception, of which only 24% use modern methods for the lack of disclosure and service and influence of socioeconomic factors (General Office Demographics, 1981). The rural population in the Andes of Peru grows continuously produces little land and few ways to make the daily basket, all of which are a challenge to their traditions, cultural values and concepts of reproduction. Some families live off the land and their livestock, but most have a small business (sale of food products) or spouses periodically migrate to find work in the city or regional agricultural communities. He divided the study group: (1) non-users, (2) users of traditional and natural methods, and (3) users of modern methods of contraception.